Impacts on the health of caregiver mother of children with cancer (Research, Society and Development, 2021)
Objective: map the scientific productions about the health impacts of women mother caregivers of children/adolescents with cancer. Methodology: integrative literature review, performed in the computerized bases of the Virtual Health Library (VHL) in May 2020. The research question was "What are the impacts on the health of women mother caregivers of children/adolescents with cancer? Results: 46 articles were found investigating the health of the mother-child caregiver with cancer and with the application of inclusion and exclusion criteria 8 studies were selected. The mother-women are the main caregivers, which causes the maternal overload and sickness expressed in the areas: physical, financial, social, information, moral and emotional. Conclusion: The health of the mother-caregiver is greatly affected, with emotional illness being the most significant aspect. This is an area of research that is still new in the nursing scenario and needs to continue to advance. New research needs to be carried out, in search of a better understanding about the needs of this population.